What is the State of the Art on UX Data Visualization? A Systematic Mapping of the Literature - Lucas Katib do Amaral; Maylon Macedo; Luciana Zaina (Journal on Interactive Systems)
From a Human-Computer Interaction perspective, data visualizations are visual representations of data that improve users' cognitive capabilities during a task. In particular, UX data visibility can raise a team's engagement with the UX design and better inform product decisions. However, researchers and professionals lack a foundation to build new UX data visualizations. In this context, this paper describes a Systematic Mapping of the Literature that aims to consolidate the state of the art on UX data visualizations. To guide the open coding of the findings, we defined ten questions that span the Visual Information Seeking Mantra and the four levels of Munzner's analysis framework. We identified 28 well-known and seven custom chart formats, with the node-link diagram arising as the most popular. Most of the visualized data comes from software logs, and there is a lack of exploration of UX metrics, acoustic data, and demographic data as data sources. Regarding the Visual Information Seeking Mantra, visualizations had a zoom and filter function and a details on demand function for most chart formats. However, most chart formats lacked overview functions. Our findings provide a broad overview of the literature that can support the creation of new UX data visualizations.